The Role of Extrinsic Motivation as a Mediator between Job Market Considerations and Financial Rewards for Student Career Selection - Tantular, Aulia Putri; Mardi; Fauzi, Achmad (First Ciera Publisher, 2023)
This study aims to determine the effect of labor market considerations and financial rewards on career selection by mediating extrinsic motivation. This study uses primary data with an affordable population of 136 Economics Education students with a concentration in Accounting at Jakarta State University in 2018-2020. The sample selection was carried out using a proportional random sampling technique which resulted in 101 Economics Education students with a concentration in Accounting at Jakarta State University. The data collection technique used was a questionnaire. The collected data will be analyzed using Microsoft Excel and IBM SPSS Statistics 26 software. Data analysis techniques performed include multiple regression analysis, path analysis, and sobel test. The results of this study indicate that there is a positive and significant influence on labor market considerations and financial rewards on career selection mediated by extrinsic motivation.